Determination of Resistance of Winter Wheat Varieties Against Root and Crown Rot Fusarium culmorum Under the Artificial Drought Conditions - Fatih Özdemir (Turkish Journal of Agriculture: Food Science and Technology)
This study was conducted to investigate the relationship between the recent increase in the frequency of drought conditions and Root-Crown Rot (Fusarium pseudograminearum, Fusarium culmorum) in rainfed wheat growing areas of Central Anatolia. In 2018, the experiment was established in the greenhouse of Konya Bahri Dağdaş International Agricultural Research Institute using 25 registered wheat varieties in a randomised block split-plot experimental design with 4 replications. Irrigation levels (100% field capacity and 50% field capacity) were designed as main plots, inoculation (+ and -) as subplots and varieties as sub-subplots. In the study, the response of the cultivars to inoculation under artificial drought conditions was evaluated by measuring Crown Score (CR), Lesion Length (LL), Number of Diseased Leaves from outside to inside (NDL) and Plant Height (PH) from five plants in each pot. Statistically, the differences between inoculation, irrigation, NDL and LL were found to be significant at P<0.0001 level, while the differences between varieties were found to be significant at P<0.001 level for the CR parameter. On the other hand, when the interactions were evaluated for the NDL parameter, the differences were found to be significant at P<0.0001 level for all three interactions of cultivar*inoculation, cultivar*irrigation and cultivar*inoculation*irrigation. When the effect of reduced water application intended to be used in resistance breeding was evaluated for 25 different varieties under Fusarium culmorum inoculation, there was an increase in CR from 41,7% (Gerek-79) to 487,5% (Altay-2000), NDL from 7,14% (Kirgiz-95) to 200% (Alpu-2001), LL from -36,84% (Karahan-99) to 283,33% (Altay-2000) and in PH reduction from 12,41% (Seval) to 32,22% (Kirgiz-95). The results showed that drought-stressed plants were already weakened and therefore more easily and severely infected by pathogens. According to these results, it has been determined that it is very important for the region to obtain resistance to drought and crown rot diseases, which have such an obvious relationship, in breeding studies.